Preclinical Validation of 99mTc–Annexin A5–128 in Experimental Autoimmune Myocarditis and Infective Endocarditis: Comparison with 99mTc–HYNIC–Annexin A5. Issue 1 (1st January 2015) - Benali, Khadija; Louedec, Liliane; Azzouna, Rana Ben; Merceron, Olivier; Nassar, Pierre; Al Shoukr, Faisal; Petiet, Anne; Barbato, Donato; Michel, Jean-Baptiste; Sarda-Mantel, Laure; Le Guludec, Dominique; Rouzet, Francois
Hydrazinonicotinamide–annexin A5 (HYNIC-Anx), a 99m technetium ( 99m Tc)-labeled agent targeting phosphatidylserine, proved to be sensitive for the detection of apoptosis and thrombosis but is no longer available for clinical use. A mutant of human annexin designed for direct 99m Tc labeling (referred to as Anx A5–128) showed improved binding affinity to phosphatidylserine and is expected to be used in humans. We compared both radiotracers with regard to pharmacokinetics and diagnostic ability in animal models. Biodistribution studies were performed in normal rats. Radiolabeled Anx A5–128 and HYNIC-Anx were compared in cardiovascular settings involving phosphatidylserine expression: experimental autoimmune myocarditis and infective endocarditis. Initial blood clearance was faster for Anx A5–128 than for HYNIC-Anx, and tissue biodistribution was similar overall for both tracers. The diagnostic sensitivity of Anx A5–128 was excellent and comparable to that of HYNIC-Anx. Anx A5–128 showed biodistribution and diagnostic ability similar to those of the HYNIC-Anx derivative, supporting its translation to clinical use.